Labor Market Transitions of Members of Opposite-Sex Couples: Nonparticipation, Unemployed Search, and Employment - Hans Bloemen (Institute of Labor Economics (IZA), 2021)
An empirical analysis of labor market transitions for spouses in couples is implemented. Object of study are transitions between the states of nonparticipation, unemployed search, and employment. Motivated by a model of household search, the emphasis is on spousal variables and interactions. Additionally, a proxy for the business cycle is included in the analysis, and household specific unobserved heterogeneity is accounted for. Results show that female transitions into nonparticipation (both out of unemployed search and employment) are positively affected by the husband's income (while no effect is found for transitions out of nonparticipation). Men seem to move from employment into unemployed search easier the higher is the wife's income. Since the wife having an income is in turn strongly accociated with female participation, this suggests that households with a participating wife are better able to deal with unemployment of the husband. A supplementary analysis with reservation wages and numbers of applications points in the same direction. Husbands' reservation wages are only sensitive to his own unemployment income if the wife is nonparticipating. This implies that unemployment benefits have a different role in households with the husband as a sole earner compared to dual earner households.
Keywords: D10; J64; C33; J20; 330; household behavior and family economics; job search; labor market transitions; panel data